The Role of ‘1+X’ Certification in Curriculum Reform and Competency-Based Education in China’s Vocational Colleges - Zhenping Sun (Journal of Advanced Research in Education, 2025)
The ‘1+X’ certification system is a major reform in China’s vocational education, designed to integrate competency-based learning with traditional academic programs. By allowing students to obtain industry-recognized certifications alongside their diplomas, the system aims to enhance workforce readiness, bridge skills gaps, and improve employment prospects. This paper examines the development, implementation, and challenges of the ‘1+X’ system, assessing its impact on curriculum integration, skill development, and industry collaboration. Findings suggest that the system has successfully expanded vocational training opportunities, enabling students to acquire practical, job-relevant skills through modular and progressive certification pathways. Employer engagement in certification design has improved graduate employability, particularly in technology-driven sectors such as IT, advanced manufacturing, and finance. However, challenges remain, including uneven certification recognition, faculty training gaps, and infrastructure limitations in vocational institutions. To maximize the effectiveness of the ‘1+X’ system, future policy recommendations include strengthening national standardization, increasing digital learning adoption, enhancing faculty upskilling programs, and fostering greater industry-academic collaboration. Expanding certification pathways into emerging industries and international labor markets will further solidify the system’s role in China’s evolving education and workforce landscape. As the country advances its commitment to lifelong learning and skills-based economic growth, the ‘1+X’ certification system stands as a key initiative in aligning vocational education with real-world job demands.